Incorporation of In Vitro Synthesized Reovirus Double-Stranded Ribonucleic Acid into Virus Corelike Particles - Sakuma, S. (1972)
When reovirus double-stranded ribonucleic acid (dsRNA) was synthesized in vitro by using a large-particulate fraction (LP-fraction) from reovirus-infected L cells, a significant amount of the (3)H-labeled dsRNA product was incorporated into reovirus corelike particles bound to the LP fraction. These corelike particles were found to be indistinguishable from virus core derived by chymotryptic digestion of virions when compared on the basis of their (i) resistance to chymotryptic digestion, (ii) buoyant density in CsCl, (iii) particle size as determined by agarose chromatography, (iv) elution characteristics from diethylaminoethyl-Sephadex, and (v) resistance of the incorporated (3)H-dsRNA to ribonuclease digestion in 0.01 m NaCl. When the replicase reaction was partially inhibited by NaCl, there was an accumulation of particles that were less dense than the virus core. All of the results indicate that some virus core assembly takes place during the in vitro replicase reaction.